Emergent salvage surgery for massive hemoptysis after proton beam therapy for lung cancer: a case report - Haruaki Hino; Kahori Nakahama; Makoto Ogata; Kayoko Kibata; Chika Miyasaka; Takahiro Utsumi; Natsumi Maru; Hiroshi Matsui; Yohei Taniguchi; Tomohito Saito; Koji Tsuta; Tomohiro Murakawa (Surgical Case Reports, 2021)
Abstract Background Salvage surgery is an effective therapeutic option for patients experiencing relapses after chemoradiotherapy for advanced-stage lung cancer or after high-dose radiotherapy for early-stage lung cancer. We report a case involving an emergent salvage surgery for a patient with massive hemoptysis who developed lung cancer recurrence after undergoing proton beam therapy 7 years prior to presentation. Case presentation A 70-year-old male patient was emergently admitted due to massive hemoptysis. He had undergone proton beam therapy for a stage I adenocarcinoma of the left upper lobe 7 years ago, and was receiving chemotherapy for local recurrence. We performed an emergent salvage pulmonary resection to achieve hemostasis. During the operation, we confirmed the presence of a left broncho-pulmonary arterial fistula, which was considered as the origin of the massive hemoptysis. We repaired the fistula between the pulmonary artery and left upper bronchus without incident; an orifice of the fistula at the left pulmonary artery was sutured using a non-absorbable monofilament, and the central portion of the orifice of the fistula at the left upper bronchus was closed with a mechanical stapling device. The postoperative diagnosis was of an adenocarcinoma—ypT3(pm1) N0M1a (dissemination)-IVA, ef1b. The patient has survived for over a year with the cancer in almost complete remission following the administration of an epidermal growth factor receptor tyrosine kinase inhibitor. Conclusions Emergent salvage surgery demands high skill levels with optimal timing and correct patient selection. Our case suggested that the procedure played an important role in controlling serious bleeding and/or infectious conditions. Consequently, he could receive chemotherapy again and survive for over a year.